Contribution of Mechanical Activation on the Growth of Intermetallic Compound Layers at the Cu/Al Interface During Vacuum Hot Pressing - Wu, Shao-peng; Cai, Xiao-lan; Zhou, Lei; Yang, Chang-jiang; Li, Wen-hao; Cheng, Yuan-chao (Transactions of the Indian Institute of Metals, 2022)
In the present paper, the Cu/Al diffusion couples were successfully prepared using high-energy ball milling and vacuum hot pressing sintering. The aim of this study was to investigate the influence of mechanical activation on the growth of intermetallic compound layers at the Cu/Al interface during hot pressing. Various results were obtained via X-ray diffractometry and field emission scanning electron microscopy analysis. Results showed that from the Cu side to Al side, Cu 9 Al 4 , CuAl, and CuAl 2 phases can be identified successively at the interface. In particular, a large number of pores are dispersed in the Cu matrix and Cu 9 Al 4 layer of the samples after ball milling, and the interface between Cu and Cu 9 Al 4 phase is blurred. In addition, compared with the unmilled sample, the thickness of the intermetallic compound layer at the Cu/Al interface of the ball-milled sample increases significantly. In terms of a single layer, although mechanical activation can improve atomic diffusivity, the growth of intermetallic compound layer is also affected by holding time. Due to the different relative positions of various intermetallic compounds at the interface, the thickness of the intermetallic compound layer near the Cu side increases significantly with a shorter holding time, while the thickness of the intermetallic compound layer near the Al side requires a longer holding time.